Nigerian Audience Views on Mainstream Media and Moulding of Public Opinion in the 21st Century - Obiorah I. Edogor; Emeka C. Odogwu; Gloria N. Chukwuemeka; Uche Nworah; Chinwe R. Okoyeocha (Athens Journal of Mass Media and Communications)
The mass media have been long known to shape and mould public opinion in every human society. However, with the influence of web 2.0 technologies that have affected mainstream journalism practice in the 21st century, this study investigated the extent to which mainstream media still mould public opinion in Nigeria. The paper was anchored on agenda-setting and media dependency theories as it investigated journalism’s ability to mould the views of people on issues of public concern. The survey research design was used where the multi-stage sampling technique was adopted and an online Australian Calculator was used to draw the sample size of 371, the questionnaire was deployed as the instrument for data collection. The results among other things revealed that, though social media and blogs’ usage have influenced mass media and public communication generally, mainstream journalism still moulds public opinion in Nigeria. This was revealed as respondents disclosed that in making decisions, they believe and use more information they obtained from mainstream media platforms than information they got from blogs and social media sites.